2016
DOI: 10.1155/2016/7079487
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Prevents Iodinated Contrast Media‐Induced Acute Renal Injury in Rats via the PI3K/Akt/Nrf2 Pathway

Abstract: Contrast-induced acute renal injury (CI-AKI) has become a common cause of hospital-acquired renal failure. However, the development of prophylaxis strategies and approved therapies for CI-AKI is limited. Salvianolic acid B (SB) can treat cardiovascular-related diseases. The aim of the present study was to assess the effect of SB on prevention of CI-AKI and explore its underlying mechanisms. We examined its effectiveness of preventing renal injury in a novel CI-AKI rat model. Compared with saline, intravenous S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 51 publications
4
52
0
Order By: Relevance
“…Salvianolic acid B has been found to be anti-inflammatory, antioxidative and anti-fibrotic, especially in experimental models of renal and liver fibrosis [7,8]. Previous research has demonstrated that SalB attenuated CCl 4 -induced hepatic fibrosis [9] and inhibited TGF-b1 activation of hepatic stellate cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Salvianolic acid B has been found to be anti-inflammatory, antioxidative and anti-fibrotic, especially in experimental models of renal and liver fibrosis [7,8]. Previous research has demonstrated that SalB attenuated CCl 4 -induced hepatic fibrosis [9] and inhibited TGF-b1 activation of hepatic stellate cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with earlier reports demonstrating that Sal B can activate Nrf2 pathway in several other organ systems. Among them, the liver [34,35], lung [36], brain [37], kidney [38], and vascular endothelial cells [19] have all been shown to be protected by Sal B pretreatment via up-regulating Nrf2 and its downstream phase II detoxification genes. Our data and these reports all indicated that Sal B can act as a potent activator of Nrf2 both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, in addition to HO-1, other antioxidant enzymes are also critical for maintaining cellular redox homeostasis against oxidative insults. Intriguingly, SalB was shown to induce activation of the Nrf2 signaling pathway in a variety of disease models [15,26,27]. Additionally, SalB is a potent activator of sirtuin 1 (SIRT1) [12,28,29], a nicotinamide adenine dinucleotide-dependent deacetylase implicated in a wide range of cellular functions.…”
Section: Introductionmentioning
confidence: 99%